The Complexity of E-Marketing and Its Influence on the Performance of Gas Companies in Tanzania: Insights from Innovation Diffusion Theory - Yohana, Augustino; Shayo, France; Mbura, Sophia (European Scientific Journal, ESJ, 2025)
This paper focuses on investigating the complexity of electronic marketing on the performance of gas energy companies in Tanzania, with insight from Innovation Diffusion Theory. Data were gathered using a structured questionnaire administered to a convenience sample of 302 employees from Gas Company Tanzania Ltd, Taifa Gas Ltd, Lake Gas Ltd, Oryx Gas Ltd, and Pan African Energy Ltd. The study employed an explanatory research design. Structural equation modeling was applied to analyze the data and identify the causal link between company performance and the complexity of electronic marketing. Results show a standardized path coefficient of .388 for COMPL5 <— COMPL, indicating that COMPL5 is a key reference indicator for the construct COMPL. Additionally, the path coefficients for COMPL1 <— COMPL (1.838, CR = 5.777, p < 0.001) and COMPL2 <— COMPL (1.960, CR = 5.685, p < 0.001) provide strong evidence of significant relationships. The high critical ratios and statistical significance of these paths further support the conclusion that the complexity of electronic marketing positively influences the performance of gas energy companies in Tanzania. The study concluded that electronic marketing directly influences the performance of gas companies through the complexity of technology. These results advise businesses in the gas sector to prioritize investments in training programs to enhance the ease of learning and application of electronic marketing tools. Organizations should also ensure that staff has access to structured learning opportunities and user-friendly systems. Reducing the entry barrier for staff through simplified tool interfaces and consistent training can help maximize their efficiency in using electronic marketing solutions. Gas businesses should also focus on developing internal knowledge and fostering a culture of appreciation for the advantages of electronic marketing.